Emerging applications of stereotactic body radiotherapy. (May 2014) - Lo, Simon S; Loblaw, Andrew; Chang, Eric L; Mayr, Nina A; Teh, Bin S; Huang, Zhibin; Yao, Min; Ellis, Rodney J; Biswas, Tithi; Sohn, Jason W; Machtay, Mitchell; Sahgal, Arjun
ABSTRACT: : Stereotactic body radiotherapy (SBRT) has been used extensively in patients with lung, liver and spinal tumors, and the treatment outcomes are very favorable. For certain conditions such as medically inoperable stage I non-small-cell lung cancer, liver and lung oligometastases, primary liver cancer and spinal metastases, SBRT is regarded as one of the standard therapies. In the recent years, the use of SBRT has been extended to other disease conditions and sites such as recurrent head and neck cancer, renal cell carcinoma, prostate cancer, adrenal metastasis, pancreatic cancer, gynecological malignancies, spinal cord compression, breast cancer, and stage II–III non-small-cell lung cancer. Preliminary data in the literature show promising results but the follow-up intervals are short for most studies. This paper will provide an overview of these emerging applications.